Manajemen Pembelajaran Berdiferensiasi pada Sekolah Dasar Penggerak Se-Kecamatan Amahai - Lautloly, Benedikta; Papilaya, J.; Lekatompessy, J.E; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Learning should be a meaningful activity, namely the liberation to actualize the full potential of students' humanity, transforming the value of knowledge in a meaningful context and easy to implement in real life, not the other way around. Differentiated learning is learning that is rooted in fulfilling the needs of students both in terms of learning readiness, interests, or learning profiles and how teachers respond to learning needs. One of the problems in the world of education, especially Elementary Schools in Amahai District, has been the weak innovation in learning. This study aims to explain (1) Planning for differentiated learning, (2) Mechanisms taken in creating, formulating, and implementing differentiated learning, (3) Monitoring and effectiveness of differentiated learning, and (4) Supporting and inhibiting factors for differentiated learning at Elementary Schools in Amahai District, Maluku Tengah Regency. The result of this research showed that: (1) Lesson plan was conducted by mapping the learning needs of students for knowing the students’ learning need. Afterwards, they worked together to formulate the Operational Curriculum Education Unit (KOSP) in order to create and determine the flow of learning objectives. Then, teachers established a Learning Community to prepare learning tools such as Lesson Plans (RPP), and Learning Modules. (2) The implementation was conducted through the understanding comprehensively of Merdeka Curriculum knowledge so that the teachers understood and realized the concept, method and strategy in differentiated learning. The mechanisms for creating, formulating and implementing differentiated learning was that teachers implemented learning by using differentiated strategy in content, process, product and learning environment . (3) The School Principal's monitoring role in fulfilling tasks and leadership responsibilities effectively in differentiated learning included: the availability of Merdeka Curriculum Textbooks, creating facilities and infrastructure for supporting differentiated learning, and the participation of teachers in workshops, socialization, and training as avenues for professional development. (4) Supporting factors included training and workshop for teachers’ mover, the next was the support from the school principal, school committee, and parents. Additionally, the supported environment and the cooperation among teachers in Teacher Work Group (KKG) in the implementation of differentiated learning. The obstacles factors covered limited time for completing differentiated learning and an insufficient number of learning resources provided by the school to meet learning needs.